. - Hanazaki, Natalia (2003)
Local ecological knowledge can be of great importance to conservation and management and especially, to the involvement of local peoples in efforts towards the conservation of biodiversity.  In this paper, brief considerations are made about the concepts of management and conservation, and management.  It is recommended that the debates about local ecological knowledge should be even more attached to the discussions about biodiversity conservation and management than they are currently.  Misconceptions about the unavoidable harmful effects of human populations on nature, as well as fuzzy images of local populations living “harmonically” with nature, should be abandoned. The efforts towards conservation should be also addressed to the socio-economic issues of the populations who directly depend on this biodiversity.